Flexural and tensile moduli of unidirectional hybrid epoxy composites reinforced by S-2 glass and T700S carbon fibres - Dong, Jonathan; Davies, Ian (Elsevier, 2014)
A study on the flexural and tensile moduli of S-2 glass and T700S carbon fibre reinforced hybrid epoxy composites in intra-ply configurations is presented in this paper. Finite element analysis (FEA) and Classic Lamination Theory (CLT) were employed to model the flexural behaviour of hybrid composites, which was obtained from the three point bend test in accordance with ASTM: D790-10 at various span-to-depth ratios. The flexural moduli were obtained from the load–displacement curves. The models were validated against the experimental results from a previous study. With the aid of the developed models, the effects of fibre volume fractions, hybrid ratio and span-to-depth ratio were studied. The results show that flexural modulus increases when the span-to-depth ratio is increased from 16 to 32 and becomes stable as the span-to-depth ratio further increases. Since the modulus of glass fibres is much lower than that of carbon fibres, both flexural and tensile moduli decrease with increasing hybrid ratio. From the full carbon/epoxy laminate, when a carbon/epoxy lamina close to the outermost surface of the laminate is replaced by a glass/epoxy lamina, the flexural modulus decreases rapidly. This is due to the maximum tensile and compressive stresses occur at the two faces of the laminate in bending, and the stresses around the mid-plane are close to zero. Tensile modulus decreases with increasing hybrid ratio. Under tension, the stress distribution is determined by the relative difference in the tensile moduli of the carbon/epoxy and glass/epoxy laminas. If the difference is small, tensile modulus versus the hybrid ratio resembles a linear relationship and no significant hybrid effects exist; if the difference is large, a strong non-linear relationship is present and large hybrid effects exist. Simple mathematical formulas are presented for calculation of the flexural and tensile moduli of hybrid composites from the moduli of the carbon/epoxy and glass/epoxy composites, and the hybrid ratio.